Oversizing of self-expanding Nitinol vascular stents – A biomechanical investigation in the superficial femoral artery. (August 2022) - Bernini, Martina; Colombo, Monika; Dunlop, Craig; Hellmuth, Rudolf; Chiastra, Claudio; Ronan, William; Vaughan, Ted J.
Abstract: Despite being commonly employed to treat peripheral artery disease, self-expanding Nitinol stents are still associated with relatively high incidence of failure in the mid- and long-term due to in-stent restenosis or fatigue fracture. The practice of stent oversizing is necessary to obtain suitable lumen gain and apposition to the vessel wall, though it is regarded as a potential cause of negative clinical outcomes when mis-sizing occurs. The objective of this study was to develop a computational model to provide a better understanding of the structural effects of stent sizing in a patient-specific scenario, considering oversizing ratio OS, defined as the stent nominal diameter to the average vessel diameter, between 1.0 and 1.8. It was found that OS  < 1.2 resulted in problematic short-term outcomes, with poor lumen gain and significant strut malapposition. Oversizing ratios that were in the range 1.2 ≤  OS ≤ 1.4 provided the optimum biomechanical performance following implantation, with improved lumen gain, reduced incomplete stent apposition and favourable predicted long-term fatigue performance. Excessive oversizing, OS  > 1.4, did not provide any further benefit in outcomes, showing limited increases in lumen gain and unfavourable long-term performance, with higher mean strain values predicted from the fatigue analysis. Therefore, our findings predict that the optimal oversizing ratio for self-expanding Nitinol stents is in the range of 1.2 ≤  OS ≤ 1.4, which is similar to clinical observations, with this study providing detailed insight into the biomechanical basis for this. Graphical abstract: Figure 1. Graphical abstract: (a) configurations of stent deployed in patients A and B; (b) short-term outcomes according to oversizing ratio ( OS ); (c) long-term outcomes according to oversizing ratio ( OS ). Image 1 Highlights: Validated FE model for assessing effects of oversizing of self-expanding Nitinol stents in superficial femoral arteries. Selection of objective and clinically-relevant parameters to assess the procedural outcomes in the short- and long term. Identification of a proper stent-to-artery diameter ratio in the range between 1.2 and 1.4 for optimal procedural outcomes. Patient-specific anatomical features have a relevant impact on the post-implantation configuration and long-term behaviour.